Beyond citation analysis: a model for assessment of research impact. - Sarli CC; Dubinsky EK; Holmes KL (Journal of the Medical Library Association, 2010)
QUESTION: Is there a means of assessing research impact beyond citation analysis? SETTING: The case study took place at the Washington University School of Medicine Becker Medical Library. METHOD: This case study analyzed the research study process to identify indicators beyond citation count that demonstrate research impact. MAIN RESULTS: The authors discovered a number of indicators that can be documented for assessment of research impact, as well as resources to locate evidence of impact. As a result of the project, the authors developed a model for assessment of research impact, the Becker Medical Library Model for Assessment of Research. CONCLUSION: Assessment of research impact using traditional citation analysis alone is not a sufficient tool for assessing the impact of research findings, and it is not predictive of subsequent clinical applications resulting in meaningful health outcomes. The Becker Model can be used by both researchers and librarians to document research impact to supplement citation analysis.